Explicit tanítás vagy imitálás? A szótagösszevonás és az átszótagolás lehetséges fejlesztésének vizsgálata magyar ajkú spanyol nyelvtanulók beszédprodukciójában - Szabó-Kovács, Dorottya (Kultúratudományi Szemle, 2023)
In this study, I am looking for possible methods to improve the application of synalepha and resyllabification in the speech of learners of Spanish. This investigation aims to compare the effects of (a) explicit teaching, that is, making the informants aware of the two phenomena and providing an opportunity to practice them, and (b) exposition to and imitation of the oral production of native speakers. The reading of ten B1-B2 CEFR level Hungarian university students has been analysed concerning the synalepha and resyllabification before and after they have participated in a brief individual training on the suprasegmental features in question or have been exposed to an authentic audio recording. According to the obtained results, explicit training seems to be more efficient when it comes to the application of synalepha and resyllabification in speech.